Template-Sacrificing Synthesis of Ni-Co Layered Double Hydroxides Polyhedron as Advanced Anode for Lithium Ions Battery - Lu, Youjun; Du, Yingjie; Li, Haibo (Frontiers in Chemistry, 2020)
The novel hollowed Ni-Co layered double hydroxide polyhedron (H-(Ni, Co)-LDHP) is synthesized via a template-sacrificing approach using ZIF-67 as template. The morphology, crystallinity, porous texture and chemical state of H-(Ni, Co)-LDHP are examined. It demonstrates that the H-(Ni, Co)-LDHP not only provides rich redox sites but also promotes the kinetics due to presence of numerous rational channels. As a result, the H-(Ni, Co)-LDHP manifests the desirable lithium ions storage performance when employed as anode. This study paves a new way for preparing hollowed nanostructure towards advanced electrochemical applications.